Apostasy and Jewish identity in High Middle Ages Northern Europe 'Are you still my brother?' - Goldin, Simha (Manchester University Press, 2014)
The attitude of Jews living in the medieval Christian world to Jews who converted to Christianity or to Christians seeking to join the Jewish faith reflects the central traits that make up Jewish self-identification. The Jews saw themselves as a unique group chosen by God, who expected them to play a specific and unique role in the world.This study researches fully for the first time the various aspects of the way European Jews regarded members of their own fold in the context of lapses into another religion. It attempts to understand whether they regarded the issue of conversion with self-confidence or with suspicion, and whether their attitude was based on a clear theological position, or on issues of socialisation.The book will primarily interest students and lecturers of Jewish/Christian relations, the Middle Ages, Jews in the Medieval period, and inter-religious research.